Third Patient With Biallelic Variants in SMAD6 With an Overlapping Phenotype: Developmental Delays, Dysmorphic Features, and Cardiovascular Abnormalities - Madison Nemshick; Elias Oxman; Eyby Leon (American Journal of Medical Genetics Part A, 2026)
ABSTRACT SMAD6 encodes an inhibitory SMAD protein that modulates BMP and TGF‐β signaling. Heterozygous pathogenic variants in SMAD6 have been primarily associated with aortic valve disease, radioulnar synostosis, and nonsyndromic sagittal and metopic synostosis. However, only two syndromic patients with biallelic variants have been reported in the literature. We report a 4‐year‐old girl with neurodevelopmental delays, dysmorphic features, complex congenital heart disease, renal asymmetry, and arterial tortuosity. Whole exome sequencing showed two homozygous SMAD6 variants of uncertain significance: c.161G>T (p.Gly54Val) and c.1A>G (p.Met1?). This is the third patient with biallelic SMAD6 variants associated with skeletal changes, more complex cardiovascular phenotype, facial dysmorphism, and novel arterial abnormalities. This suggests biallelic variants may cause a distinct and potentially more severe autosomal recessive syndrome. Functional investigation is needed to determine the molecular consequences of biallelic SMAD6 variants and to inform variant classification and mechanism. This report characterizes a potential unique genetic syndrome associated with biallelic SMAD6 variants, highlighting the importance of additional sequencing, vascular imaging, and multidisciplinary care coordination for these patients.